Regulatory role and therapeutic prospect of lactate modification in cancer - Sun, Mengdi; Wang, Kejing; Lu, Fang; Yu, Donghua; Liu, Shumin (Frontiers in Pharmacology, 2025)
Post-translational modifications (PTMs) of proteins refer to the process of adding chemical groups, sugars, or other molecules to specific residues of target proteins following their biosynthesis by ribosomes. PTMs play a crucial role in processes such as signal transduction, epigenetics, and disease development. Lactylation is a newly discovered PTM that, due to its close association with lactate—the end product of glycolytic metabolism—provides a new perspective on the connection between cellular metabolic reprogramming and epigenetic regulation. Studies have demonstrated that lactylation plays a significant role in tumor progression and is associated with poor clinical prognosis. Abnormal histone lactylation can influence gene expression in both tumor cells and immune cells, thereby regulating tumor progression and immunosuppression. Lactylation of non-histone proteins can also modulate processes such as tumor proliferation and drug resistance. This review summarizes the latest research progress in the field of lactylation, highlighting its roles and mechanisms in tumorigenesis, tumor development, the tumor microenvironment, and immunosuppression. It also explores the potential application value of lactylation in tumor-targeted therapy and combined immunotherapy.